Fhtm2u / Amanina Mat Ghani ...[et al.] - Mat Ghani, Amanina; Wan Kamarudin, Wan Nor Bayah; Wan Nawawi, Wan Nazriah; Mohd Zaki, Mohd Izwan; Mohd Fuza, Zatul Iffah (2020)
The Faculty of Hotel and Tourism Management (FHTM), UiTM Terengganu, offers food and beverage (F&B) practical classes. The Faculty operates three mock restaurants, namely Bayu Grill, Mock Restaurant, and Kafe Kreatif. These classes are open not only to the UiTM staffs and students but also to external customers. However, customers face difficulties searching for information about the menu, venue, price, and other details offered in the practical classes. Thus, the objective of this project is to invent a user-friendly application to assist customers to select the menu, venue, price, and time of choice from these restaurants. Moreover, this innovative systematic reservation application, fhtm2U, will also provide a list of tourist attraction places for the customers to get an idea for sightseeing while visiting the UiTM Dungun campus. Also, fhtm2U has the potential to be commercialized, as it will bring in more customers. Users can download this application via Android or iOS. This application could drive up student menu sales and marketing strategy. Indirectly, it will also promote FHTM programs to the public